PROSES ADAPTASI MAHASISWA RANTAU DARI BATAM DALAM MENGHADAPI KOMUNIKASI ANTARBUDAYA DI UPNVJ: (Studi Deskriptif Mengenai Proses Adaptasi Mahasiswa Asal Batam Dalam Menghadapi Hambatan Komunikasi Antarbudaya Di UPNVJ) - Rania Putri Faradyba; Yoga Sembada, Windhiadi; Krisnando Nathanael, Garcia (Communications, 2022)
This study aims to discuss the adaptation process of out-of-province students from Batam in UPN Veteran Jakarta in facing cross-cultural communication barriers using the Communication Accommodation Theory. The study used the qualitative descriptive method using primer and secondary data; the data collecting technique was done by purposive sampling. Then the researcher used the Miles and Huberman data analysis stages which are the data reduction stage, presenting data, then drawing conclusions and verification using the triangulation method. The final result of the study shows that out-of-province students from Batam experienced the five stages of the adaptation process according to Young Y. Kim. The five stages cover Planning Phase, Honeymoon Phase, Frustration Phase, Readjustment Phase, and Resolution Phase through each other’s different experiences. Although different, they experienced similar problems in facing cross-cultural communication barriers, which are cultural differences, especially languages, customs, and lifestyle, so they experience culture shock. Therefore, out-of-province students from Batam started to develop in various ways, thus making accommodations and convergence in facing cultural differences to be able to adapt and interact comfortably in the UPNVJ environment. Keywords; adaptation process, out-of-province students, cross-cultural communication, communication accommodation theory